(untitled) (Universal International Scientific Journal, 2026)
This article conceptualizes the violation of behavioral norms in the pedagogical team of a secondary school (such as interruptions, sarcasm, disdain, neglect, and withdrawal from discussion) as a hidden managerial factor that undermines psychological safety. When behavioral norms are violated, teachers’ interpersonal risk behaviors such as asking questions, raising problems, admitting mistakes, and expressing opinions decrease; as a result, open communication and cooperation weaken, which can negatively affect the quality of decisions and the stability of implementation. The article explains this relationship through a chain of mechanisms and proposes organizational mechanisms such as standardizing behavioral standards within the framework of school management, introducing a constructive feedback procedure, strengthening transparent and explanatory decision-making practices, and establishing channels for raising problems.